Assessing Cholesterol Storage in Live Cells and C. elegans by Stimulated Raman Scattering Imaging of Phenyl-Diyne Cholesterol - Lee, Hyeon Jeong (Sci Rep, 2015)
We report a cholesterol imaging method using rationally synthesized phenyl-diyne cholesterol (PhDY-Chol) and stimulated Raman scattering (SRS) microscope. The phenyl-diyne group is biologically inert and provides a Raman scattering cross section that is 88 times larger than the endogenous C = O stretching mode. SRS microscopy offers an imaging speed that is faster than spontaneous Raman microscopy by three orders of magnitude, and a detection sensitivity of 31 μM PhDY-Chol (~1,800 molecules in the excitation volume). Inside living CHO cells, PhDY-Chol mimics the behavior of cholesterol, including membrane incorporation and esterification. In a cellular model of Niemann-Pick type C disease, PhDY-Chol reflects the lysosomal accumulation of cholesterol, and shows relocation to lipid droplets after HPβCD treatment. In live C. elegans, PhDY-Chol mimics cholesterol uptake by intestinal cells and reflects cholesterol storage. Together, our work demonstrates an enabling platform for study of cholesterol storage and trafficking in living cells and vital organisms.